Eksplorasi Faktor-Faktor yang Mempengaruhi Preferensi Pelanggan terhadap Kaizen Heritage Bekasi (International Forum of Researchers and Lecturers, 2023)
The development of the culinary industry and urban lifestyle in large cities like Bekasi is increasingly demonstrating competitive dynamics. Urban residents are not simply looking for places to eat and enjoy coffee, but also for social spaces that offer experiences, identity, and quality tailored to customer needs. Kaizen Heritage Coffee Bekasi presents itself as a destination and lifestyle space that embraces the concept of blending heritage values. To explore the factors influencing customer preference for Kaizen Heritage Coffee Bekasi, a series of methodological steps will be undertaken, including secondary data analysis, surveys and interviews, and quantitative and qualitative data analysis. Through this qualitative approach, the research seeks to explore the experiences and perspectives of visitors to Kaizen Heritage Coffee Bekasi in depth. In depth of interviews were conducted with the 30 respondents, providing insights into key elements such as service quality, the location's atmosphere, and the values ​​espoused by Kaizen Heritage Coffee Bekasi.